The impact of transformational leadership style on nurses job satisfaction: an integrative review - Gebreheat, Gdiom (2023)
Introduction The argument about whether leadership style affects nurses’ job satisfaction is centered around the impact of different leadership styles on the work environment and the quality of care provided by nurses. Therefore, this review was primarily aimed at assessing the impact of transformational leadership style on the job satisfaction of hospital nurses. Methods This is an integrative review conducted according to the Whittemore and Knafl's framework. Comprehensive literature searches were conducted in PubMed, MEDLINE, CINAHL, Web of Science, Research4Life, and APA PsychInfo. In addition, studies were included through hand-searching from different sources of grey literature and a reference list of identified articles. All English articles published between 2012 and 2023 reporting the impact of transformational leadership style on nurses’ job satisfaction were eligible for inclusion. Results Seventeen articles were included in the review, of which 16 were cross-sectional studies, while one was mixed. The majority (n = 12) of the studies were conducted in at least two or more healthcare settings, with a total of 5841 nurses. Almost all (n = 16) articles reported the positive influence of transformational leadership on nurses’ job satisfaction. In addition, the transformational leadership style was reported to have a positive impact on nurses’ intentions to stay at work, quality care, and patient outcomes. Conclusion By adopting a transformational leadership approach within clinical environments, there is a potential to boost nurses’ job satisfaction.